PENGARUH PENAMBAHAN MONO-ASILGLISEROL (MAG) SEBAGAI EMULSIFIER PRODUK BAKERY - Dwi Setyaningsih; Jihan Suraya; Syafira Salsabila (Jurnal Teknologi Industri Pertanian, 2021)
Mono-acylglycerol (MAG) is the most used type of emulsifier in food industry. The need for domestic emulsifiers increases each year with an average value of 4%, so that the development of MAG as an emulsifier has good prospects. This study aimed to determine the best concentration of MAG as bakery products emulsifier such as sponge cake (2%, 2.5%, 3%), white bread (0.5%, 1%, 1.5%), and cookies (0.8%, 1.6%, 3.2%), and to know the characteristics differences of bakery products between synthesized MAG and commercial emulsifier. MAG was synthesized through the esterification process of coomercial glycerol from the byproducts of making biodiesel and palm fatty acid distillate from the byproducts of crude oil purification at a temperature of 150°C, 90 minutes time, and a molar ratio of PFAD:glycerol 1:6. The best MAG concentrations for sponge cake were 2.5% based on physical characteristics and 3% based on organoleptics. The best MAG concentration for white bread was 1% indicate by its swelling dimensions. The best MAG concentration for cookie was 1.6% indicated by its swelling power that affects the crispness. The addition of MAG as emulsifier produces good characteristics and equivalent to commercial MAG in several aspects of bakery product quality.Keywords: bakery, emulsifier, mono-acylglycerol, organoleptics, swelling powder